Exploring cloud-based Web Processing Service: A case study on the implementation of CMAQ as a Service. (March 2019) - Zhang, Chen; Di, Liping; Sun, Ziheng; Lin, Li; Yu, Eugene G.; Gaigalas, Juozas
Abstract: As an important tool for air quality simulation, the Community Multiscale Air Quality (CMAQ) model is widely used in the environmental modeling community. However, setting up and running the CMAQ model could be challenging for many scientists, especially when they have limited computing resources and little experience in handling large-scale input data. In this study, we explore the cloud-based Web Processing Service (WPS) and present the Cloud WPS framework to support implementing Earth science model as WPS. Specifically, to make CMAQ easier to use for scientists through the latest standard-based Web service technology, CMAQ-WS, a prototype of CMAQ as a Service, is developed and tested. The result of the experiment shows the framework significantly improves not only the performance of but also ease of use of the CMAQ model thus providing great benefits to the environmental modeling community. Meanwhile, the proposed framework provides a general solution to integrate Earth science model, WPS, and cloud infrastructure, which can greatly reduce the workload of Earth scientists. Highlights: A cloud-based Web Processing Service (WPS) framework to support environmental modeling is designed. CMAQ-WS, an open standard-based prototype of CMAQ as a Service, is implemented and tested. All components of the prototype are powered by GeoBrain Cloud and bridged by CyberConnector. The Cloud WPS framework offers a solution for scientists to access Earth science models without effort.